Income precarity and child and parent weight change during the COVID-19 pandemic: a cross-sectional analysis of the Ontario Parent Survey - Sarah Carsley; Laura N Anderson; Andrea Gonzalez; Yulika Yoshida-Montezuma; Brendan T. Smith; Marc Jambon (BMJ Open)
Objectives To describe child and parent weight change during the pandemic, overall and by income precarity.Design A cross-sectional online survey was conducted.Setting Caregivers of children 0–17 years of age living in Ontario, Canada, during the COVID-19 pandemic from May 2021 to July 2021.Participants A convenience sample of parents (n=9099) with children (n=9667) living in Ontario were identified through crowdsourcing.Primary outcome measure Parents recalled, for themselves and their child, whether they lost weight, gained weight or remained the same over the past year. OR and 95% CI were estimated using multinomial logistic regression for the association between income precarity variables and weight loss or gain, adjusted for age, gender and ethnicity.Results Overall, 5.5% of children lost weight and 20.2% gained weight. Among adolescents, 11.1% lost weight and 27.1% gained weight. For parents, 17.1% reported weight loss and 57.7% reported weight gain. Parent weight change was strongly associated with child weight change. Income precarity measures, including job loss by both parents (OR=7.81, 95% CI 5.16 to 11.83) and disruption to household food supply (OR=6.05, 95% CI 4.77 to 7.68), were strongly associated with child weight loss. Similarly, job loss by both parents (OR=2.03, 95% CI 1.37 to 3.03) and disruption to household food supply (OR=2.99, 95% CI 2.52 to 3.54) were associated with child weight gain.Conclusions Weight changes during the COVID-19 pandemic were widespread and income precarity was strongly associated with weight loss and weight gain in children and parents. Further research is needed to investigate the health outcomes related to weight change during the pandemic, especially for youth, and the impacts of income precarity.